Cardiopulmonary exercise test-based assessment of the effects of sacubitril/valsartan on the blood pressure response to exercise in patients with acute myocardial infarction during hospitalization. (4th July 2022) - Zeng, Chun-Mei; Zhao, Yan-Mei; Li, Yi-Yi; Lin, Zhi-Hai; Li, Ping; Feng, Ying; Tan, Jian-Ping; Pang, Kai-Fang
ABSTRACT: Objective: To investigate the effects of sacubitril/valsartan (S/V) on cardiopulmonary function and blood pressure response to exercise during hospitalization in patients with acute myocardial infarction (AMI) based on the cardiopulmonary exercise test (CPET). Methods: A total of 265 AMI patients were treated with either perindopril or S/V within 24 hours of admission. CPET was completed for all patients before discharge. There were 182 cases in the perindopril group and 83 cases in the S/V group. Results: The proportion of exercise oscillatory ventilation (EOV) was higher in the S/V group than in the perindopril group (10.8% vs 1.6%, X 2 = 11.148, P = .001). The resting heart rate (HR), resting diastolic blood pressure (DBP), and warm-up DBP were lower in the S/V group than in the perindopril group ( P < .05). The resting systolic blood pressure (SBP) was 9.0 mmHg lower (115.7 ± 17.5 vs 106.7 ± 15.0, P < .001), the SBP during warm-up was 9.5 mmHg lower (124.8 ± 23.7 vs 115.3 ± 22.5, P = .002), the SBP at the anaerobic threshold (AT) was 10.5 mmHg lower (135.3 ± 24.8 vs 127.1 ± 25.1, P = .021), the SBP at max watts was 11.5 mmHg lower (148.9 ± 26.4 vs 137.4 ± 26.4, P = .001), and the SBP during one-minute recovery was 12.3 mmHg lower (146.5 ± 27.1 vs 134.2 ± 24.4, P = .001)in the S/V group than in the perindopril group. The S/V group had a higher oxygen ventilation equivalent and carbon dioxide ventilation equivalent (VE/VCO2 ) at AT and a lower oxygen uptake–work rate relationship during max watts ( P < .05). The differences in the oxygen pulse, stroke volume, peak oxygen uptake (VO2 peak ), and VE/VCO2 slope were not statistically significant between the two groups. Conclusion: Treatment with S/V was able to reduce the exercise blood pressure in patients with AMI during hospitalization, but did not significantly improve the VO2 peak, VE/VCO2 slope, or exercise tolerance.